2023
DOI: 10.4103/jisp.jisp_676_21
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant macrodesign features in the past 10 years: A systematic review

Nurul Aulia Cahyaningtyas,
Aldilla Miranda,
Prajna Metta
et al.

Abstract: Dental implant is a material used in replacing missing teeth. The osseointegration process of dental implants will be affected by the macrodesign of the fixtures. This study aimed to review the dental implant macrodesign in the past 10 years. This study was conducted in a systematic review method using two electronic databases (PUBMED and Science Direct). Only randomized controlled trials (RCTs) published in the last 10 years were used for this review. All the search results were filtered using Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Due to lower primary stability, less resistance to vertical movements, and shear stresses, cylindrical implants are favorable under delayed loading (Vandamme, et al, 2008). In a systematic review conducted by Alshehri & Alshehri, F. 2016, implant shape did not differ in implant survival in the posterior maxilla (Cahyaningtyas, et al, 2023). showed that cylindrical implants did not have higher MBL after 6 months.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Due to lower primary stability, less resistance to vertical movements, and shear stresses, cylindrical implants are favorable under delayed loading (Vandamme, et al, 2008). In a systematic review conducted by Alshehri & Alshehri, F. 2016, implant shape did not differ in implant survival in the posterior maxilla (Cahyaningtyas, et al, 2023). showed that cylindrical implants did not have higher MBL after 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…Only one article compared cylindrical to conical implants and related to MBL, and another study compared two conical implants and related to MBL, but one of them has shape characteristics that are close to the cylindrical, and for that reason, the study was included. There are two types of shape (Cahyaningtyas, et al, 2023), conical implants use lateral and vertical pressure to achieve stability, while cylindrical implants rely on static friction at the base (Heimes, et al, 2023). Tapered implants facilitate clinical practice by reducing bone drilling steps, generating less surgical trauma, less bone resorption in the primary stages and accelerated bone remodeling under adequate insertion torque, better distribution of occlusal loads, less susceptibility to buccal bone drilling, and achieving higher insertion torque (Heimes, et al, 2023;Kreve, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation